2009
DOI: 10.1254/jphs.09203fp
|View full text |Cite
|
Sign up to set email alerts
|

Aggravation of Cold-Restraint Stress–Induced Gastric Lesions in Adjuvant Arthritic Rats: Pathogenic Role of Inducible and Endothelial Nitric Oxide

Abstract: Abstract. It was reported previously that non-steroidal anti-inflammatory drugs (NSAID)-induced gastric damage was markedly aggravated in rats during arthritis, and this response was mediated by the overproduction of nitric oxide (NO) derived from endothelial NO synthase (eNOS) in addition to inducible NO synthase (iNOS). The present study examined the gastric ulcerogenic response to cold-restraint stress in adjuvant arthritic rats, particularly in relation to NO /NOS isozymes. Exposure of normal rats to cold-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 34 publications
2
7
0
Order By: Relevance
“…On the other hand, intravenous injection of 1400W did not affect the resting GMBF or the GMBF increase in response to capsaicin. In agreement with our results, it has been reported that the eNOS was expressed mostly in the vasculature throughout the gastric mucosa in rats, but that expression of iNOS was hardly seen in the gastric mucosa of normal rats by using immunohistochemical analysis [11,12]. These findings support our hypothesis that eNOS/NO plays a role in the resting state of GMBF responses, while iNOS/NO plays no role in the increased GMBF in response to capsaicin.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…On the other hand, intravenous injection of 1400W did not affect the resting GMBF or the GMBF increase in response to capsaicin. In agreement with our results, it has been reported that the eNOS was expressed mostly in the vasculature throughout the gastric mucosa in rats, but that expression of iNOS was hardly seen in the gastric mucosa of normal rats by using immunohistochemical analysis [11,12]. These findings support our hypothesis that eNOS/NO plays a role in the resting state of GMBF responses, while iNOS/NO plays no role in the increased GMBF in response to capsaicin.…”
Section: Discussionsupporting
confidence: 93%
“…L -NIO was also reported to be the most potent inhibitor of the eNOS isoform, with an observed IC 50 value of 0.08 μmol/l, a value approximately 4-fold lower than that observed for iNOS (IC 50 = 0.3 μmol/l) and nNOS (IC 50 = 0.3 μmol/l) isoforms [41]. However, the selectivity of L -NIO is not very high, this agent at a high dose (>30 mg/kg) reportedly suppressed the iNOS isoform as well [12,42]. In addition, it was shown that L -NIO inhibited eNOS activity for 4 h after treatment in vivo [12].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nitrotyrosine is a product of tyrosine nitration mediated by reactive nitrogen species such as peroxynitrite anion and nitrogen dioxide (21). It is detected in a number of pathological conditions and is considered a marker of NO-dependent oxidative stress.…”
Section: Increased Level Of 4-hne-protein Adduct and Nitrotyrosine Inmentioning
confidence: 99%